Analysing the Heavy Metal Profile in Bottled Water and Sachet Water Samples from Various Markets in Lagos, Nigeria - O. E. Bolawa; O. S. Adelusi (Challenges and Advances in Chemical Science Vol. 2, 2021)
Water is a very important component of biochemical processes in the body. Drinking water should conform to standards set by the World Health Organization. Water is a life sustaining drink and it is essential for the survival of all organisms. The provision of safe drinking water is a very important public health priority. Most of the diseases in developing countries are caused by the consumption of contaminated water. The concentrations of six heavy metals and six trace metals were determined in sachet water samples and bottled water samples obtained in Lagos markets, Nigeria using Atomic Absorption Spectrophotometry (AAS). Lead concentrations were below the maximum permissible levels except in Bevap sachet water, Osan bottled water, Christo bottled water and Cway bottled water samples. Cadmium was not found in most of the water samples except in Pringad bottled water, Sunar bottled water and Cway bottle water samples together with Nimbus satchet water. These levels were above the maximum permissible levels of the WHO. Chromium was found present in all the water samples analyzed although in trace amounts. All other heavy metals analyzed were below the maximum permissible levels. The water samples also contained iron, manganese, calcium, magnesium, sodium and potassium in concentrations that are not harmful to the body. Examination of heavy metals in the water samples showed traces of lead in five sachet water samples and seven bottle water samples together with cadmium in three satchet water samples and three bottled water samples. This may be harmful after being consumed for a long time by the populace.